Ruthenium / ruthenium selenide composite material and preparation method and application thereof

The preparation of ruthenium/ruthenium selenide composite material by hydrothermal calcining method solves the problem of insufficient catalyst stability and activity in the PEMWS device, and achieves efficient hydrolysis and oxygen evolution performance of electrolytic hydrolysis, which is suitable for large-scale applications.

CN120575252APending Publication Date: 2025-09-02HEFEI CAREER TECHNICAL COLLEGE
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510751793.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-06
Publication Date
2025-09-02

AI Technical Summary

Technical Problem

The existing PEMWS devices lack dual-function electrocatalysts that have high activity and stability. Especially in acidic environments, RuO2 is prone to oxidation and inactivation and dissolution of active centers, resulting in insufficient durability of the catalyst and difficult to meet the needs of long-term and high-load operation.

Method used

The ruthenium/ruthenium selenide composite material was prepared by hydrothermal calcining. By controlling the molar ratio of ruthenium salt to selenium powder and the amount of reducing agent, Ru/RuSe2 heterojunction was generated. The synergistic action of Ru and RuSe2 was used to optimize the catalytic active site, improve the hydrogen and oxygen evolution properties of electrolytic water, and maintain the stability of the material through inert atmosphere protection.

Benefits of technology

It realizes the efficient catalytic performance of Ru/RuSe2 composite materials in acidic media, improves the stability and activity of hydrolyzed hydrogen and oxygen evolution reactions, reduces the amount of precious metals, simplifies the preparation process and reduces costs, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120575252A_ABST
    Figure CN120575252A_ABST
Patent Text Reader

Abstract

The invention discloses a ruthenium / ruthenium selenide composite material and a preparation method and application thereof, and relates to the technical field of water electrolysis catalyst materials.The preparation method comprises the following steps that ruthenium salt is dissolved in deionized water, selenium powder is added under vigorous stirring, then a reducing agent is added and stirred to be uniform, then the mixture is transferred into a reaction kettle to be subjected to a hydrothermal reaction, and the ruthenium / ruthenium selenide composite material is obtained; after the reaction is finished, centrifuging, washing and drying are performed, the obtained product is sintered in an inert atmosphere, the Ru / RuSe2 composite material is obtained, controllable synthesis of the Ru / RuSe2 composite material is achieved through a hydrothermal-calcination two-step method in combination with parameter control and inert atmosphere protection, the problem that an existing catalyst is insufficient in activity and stability in an acid environment is solved, and the Ru / RuSe2 composite material is obtained. The Ru / RuSe2 heterojunction interface is regulated and controlled through electron transfer, so that the adsorption capacity of Ru sites to HER activity is optimized, the RuSe2 sites promote intermediate conversion in the OER process, one agent has double effects, the hydrogen evolution and oxygen evolution performance of electrolyzed water is effectively improved, the use amount of precious metal is reduced by introducing selenium into the composite material, the preparation process is simple, and the cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation of water electrolysis catalyst materials, and in particular to a ruthenium / ruthenium selenide composite material and a preparation method and application thereof. Background Art

[0002] As a key secondary energy source, hydrogen, with its significant advantages of cleanliness, abundance, and sustainability, plays a vital role in global energy transition and sustainable development, becoming a research focus in the energy sector. Among hydrogen production technologies, the acidic water splitter (PEMWS), based on mature proton exchange membrane (PEM) technology, demonstrates tremendous potential. Its high proton conductivity and convenient gas separation capabilities lay the foundation for the large-scale commercialization of hydrogen energy.

[0003] However, the practical application of this technology still faces core challenges: both the anodic oxygen evolution reaction (OER) and the cathodic hydrogen evolution reaction (HER) of the PEMWS device require efficient electrocatalysts to accelerate the slow kinetic processes. The metal-based nanocatalysts that have been widely studied are prone to active center dissolution and degradation in extremely acidic environments, resulting in a significant decrease in catalytic activity and durability. Although precious metal-based materials are regarded as benchmark catalysts due to their excellent catalytic activity, their monofunctional properties have compatibility issues with the complex operating environment of the PEMWS electrolyzer, limiting their practical application. Ruthenium (Ru) has unique potential in the field of electrocatalysis due to its high cost-effectiveness, moderate binding energy with reaction intermediates, excellent thermal stability and corrosion resistance, and its oxide RuO2 is widely used as an efficient commercial OER catalyst. However, RuO2 is prone to oxidative deactivation under high-pressure conditions. The loss of lattice oxygen will trigger the dissolution of active substances, resulting in insufficient stability during the OER process, making it difficult to meet the long-term and high-load operation requirements of the PEMWS device.

[0004] The core bottleneck of existing PEMWS technology lies in the lack of bifunctional electrocatalysts that combine high activity and stability. The development of oxygen-free Ru-based catalysts, through the rational manipulation of their morphology and electronic structure, is expected to address the dissolution and deactivation of traditional catalysts in acidic media, enhance their intrinsic catalytic activity and durability, and provide an efficient and stable solution for large-scale hydrogen production. Therefore, the design of oxygen-free Ru-based bifunctional catalysts with specific morphology and electronic structure is of great practical significance for promoting the commercialization of PEMWS devices and accelerating the global energy transition. Summary of the Invention

[0005] The purpose of the present invention is to provide a ruthenium / ruthenium selenide composite material and its preparation method and application, so as to solve the problem that the existing decomposition device lacks a bifunctional electrocatalyst with both high activity and stability.

[0006] A ruthenium / ruthenium selenide composite material and a preparation method thereof, comprising the following steps:

[0007] S1. Dissolve 0.05-1g of ruthenium salt in 35mL of deionized water, add 0.05-1g of selenium powder under vigorous stirring, and stir for 5-15min to form a mixed solution. The ratio of ruthenium salt to selenium powder, combined with the amount of reducing agent, ensures the optimal molar ratio of Ru / RuSe2 and balances the HER and OER active sites. Strictly controlling the amount of raw materials can avoid byproducts or Ru elemental agglomeration caused by excessive Se and improve the purity of the catalyst;

[0008] S2. Add 2-5 mL of 85 wt% hydrazine hydrate or 0.5-1 g of NaBH4 as a reducing agent to the mixed solution in S1 and continue stirring for 20-30 min;

[0009] S3, transfer the stirred solution in S2 to a 50mL Teflon reactor and conduct a hydrothermal reaction. Through the hydrothermal reaction, the ruthenium salt is partially reduced to Ru(OH)3 under the action of the reducing agent. At the same time, the selenium powder Se and Ru 3+ The reaction generates RuSe2 nanoparticles. This mixed phase structure provides a uniform atomic distribution for subsequent calcination, which is conducive to the formation of a tightly bound Ru / RuSe2 heterojunction.

[0010] S4. After the hydrothermal reaction is completed, the product is centrifuged, washed, and dried to obtain a Ru(OH)3 / RuSe2 intermediate;

[0011] S5. The Ru(OH)3 / RuSe2 intermediate obtained in S4 is calcined at 500-700°C for 3-4h under an inert atmosphere to obtain a Ru(OH)3 / RuSe2 composite material. High-temperature calcination decomposes Ru(OH)3 into metallic Ru, and forms a close interface with the adjacent RuSe2, promoting electron transfer and synergistic catalytic effects. If the temperature is too low, the decomposition is incomplete, and if the temperature is too high, it may lead to particle sintering and a decrease in specific surface area. Calcination under an inert atmosphere ensures that RuSe2 maintains a hexagonal stable phase structure.

[0012] Preferably, the ruthenium salt used in step S1 is any one of RuCl3·xH2O, anhydrous ruthenium chloride or ruthenium acetate.

[0013] Preferably, the temperature of the hydrothermal reaction in step S3 is 150-180°C, and the reaction time is 10-15h. The temperature of the hydrothermal reaction is set to 150-180°C, so that the dissolution of Se powder and the reaction rate are moderate, the RuSe2 particle size can be controlled at the nanometer level, the specific surface area and active site density of the catalyst are increased, and the reaction time of 10-15h ensures that the reaction is fully carried out to form a uniform Ru(OH)3 / RuSe2 intermediate. The hydrothermal environment can induce the generation of layered or porous structured intermediates, providing a rich active interface for the composite material after subsequent calcination.

[0014] Preferably, the inert atmosphere used in step S5 is argon or nitrogen.

[0015] Preferably, the inert atmosphere is argon, which prevents Ru from being oxidized to RuO2 and inhibits the volatilization and oxidation of Se, thereby ensuring the stability of the chemical composition and crystal structure of the composite material.

[0016] Preferably, the Ru / RuSe2 composite material is a hexagonal stable phase material. This crystal form has good electrical conductivity and structural stability, is suitable for water electrolysis reaction, and can maintain a certain stability in different media.

[0017] The present invention also provides the use of the ruthenium / ruthenium selenide composite material described in the above technical solution or the ruthenium / ruthenium selenide composite material obtained by the preparation method described in the above technical solution as a catalyst in hydrogen production by electrolysis of water.

[0018] The advantages of the present invention are as follows: a ruthenium / ruthenium selenide composite material and its preparation method and application in the present invention realize the controllable synthesis of Ru / RuSe2 composite material through a two-step hydrothermal-calcination method, combined with precise parameter control and inert atmosphere protection, and solve the problem of insufficient activity and stability of existing catalysts in acidic environments. The Ru-based material has good catalytic activity and can effectively improve the performance of hydrogen and oxygen evolution in electrolysis of water. It is highly practical and utilizes the synergistic effect of Ru and RuSe2 to achieve the best catalytic benefit under controllable costs. The Ru / RuSe2 heterojunction interface is regulated by electron transfer to make the Ru site By optimizing the adsorption capacity for HER activity, RuSe2 sites promote the conversion of intermediates in the OER process, achieving dual effects in one dose. At the same time, the presence of RuSe2 protects Ru metal from corrosion in acidic media. The stability of the hexagonal phase structure can resist lattice oxygen loss and significantly improve the life of the catalyst. Through clear raw material ratios, reaction temperature and time parameters, the consistency of catalyst performance between batches is ensured, and the technical threshold for large-scale production is lowered. Compared with pure precious metal catalysts, Ru / RuSe2 composite materials reduce the use of precious metals through the introduction of selenium while maintaining high activity. The preparation process is simple and the cost is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is an X-ray photoelectron spectroscopy analysis diagram of the Ru / RuSe2 composite material prepared in Example 1.

[0020] Figure 2 This is a transmission electron microscope image of the Ru / RuSe2 composite material prepared in Example 1.

[0021] Figure 3 This is the oxygen evolution performance diagram of the Ru / RuSe2 composite material prepared in Example 1.

[0022] Figure 4 This is a diagram showing the hydrogen evolution performance of the Ru / RuSe2 composite material prepared in Example 1.

[0023] Figure 5 This is the X-ray photoelectron spectroscopy analysis diagram of the Ru material prepared in Comparative Example 1.

[0024] Figure 6 This is the oxygen evolution performance diagram of the Ru material prepared in Comparative Example 1.

[0025] Figure 7 This is a diagram of the hydrogen evolution performance of the RuSe2 material prepared in Comparative Example 2. DETAILED DESCRIPTION

[0026] In order to make the technical means, creative features, objectives and effects achieved by the present invention easier to understand, the present invention is further described below in conjunction with specific implementation methods.

[0027] Example 1

[0028] In this embodiment, the Ru / RuSe2 composite material was prepared according to the following steps:

[0029] (1) Dissolve 0.05 g of RuCl3·xH2O in 35 mL of deionized water. Add 0.05 g of selenium powder under vigorous stirring and stir for 10 min. Add 2 mL of 85 wt% hydrazine hydrate dropwise under stirring and stir for 30 min. Transfer the mixture to a 50 mL Teflon reactor and hydrothermally react at 180 °C for 12 h. After the reaction, centrifuge, wash, and dry to obtain a Ru(OH)3 / RuSe2 intermediate.

[0030] (2) Ru(OH)3 / RuSe2 was calcined at 650°C for 3 h under an argon atmosphere to obtain a Ru / RuSe2 composite material.

[0031] Figure 1 This is an X-ray photoelectron spectroscopy (XPS) analysis of the Ru / RuSe2 composite material prepared in this embodiment. It can be seen that the obtained material is Ru / RuSe2.

[0032] Figure 2 This is a transmission electron microscope (TEM) image of the Ru / RuSe2 material prepared in this embodiment. It can be seen that the material has a hexagonal phase structure. The hexagonal stable phase structure ensures that the crystal structure integrity is maintained in different media such as acid / alkali, resists catalyst dissolution and deactivation, and extends the service life.

[0033] The Ru / RuSe2 composite material prepared in this example was used as a water electrolysis catalyst material to test its performance of hydrogen and oxygen evolution in water electrolysis. The sample preparation and testing method are as follows: 10 mg of catalyst, 2 mg of KB and 40 μL of naphthol were dissolved in 2 mL of isopropanol aqueous solution (V异丙醇 :V 水 =1:5) and ultrasonicated for 1 hour to form a homogeneous mixed solution. 3 μL of the solution was dropped onto a glassy carbon electrode and air-dried for 2 hours to form a catalyst layer. LSV testing was performed on a disk electrode.

[0034] Figure 3 The oxygen evolution performance diagram of the Ru / RuSe2 composite material of this embodiment shows that it provides 10mAcm -2 For a current density of 100 nm, Ru / RuSe2 only requires an overpotential of 268 mV.

[0035] Figure 4 The hydrogen evolution performance diagram of the Ru / RuSe2 composite material of this embodiment shows that when the voltage reaches -0.4V (vsRHE), the current density reaches -63mAcm -2 .

[0036] Example 2

[0037] In this example, a Ru / RuSe2 composite material was prepared in the same manner as in Example 1, and its hydrogen and oxygen evolution performances in water electrolysis were tested, with the only difference being that the mass of the selenium powder in step (1) was 0.1 g.

[0038] After testing, the Ru / RuSe2 composite material based on this embodiment provides 10mAcm in the oxygen evolution performance test. -2 A current density of 296 mV is required.

[0039] Example 3

[0040] In this example, a Ru / RuSe2 composite material was prepared in the same manner as in Example 1, and its hydrogen and oxygen evolution performances in water electrolysis were tested, with the only difference being that the calcination temperature in step (2) was 500°C.

[0041] After testing, the Ru / RuSe2 composite material based on this embodiment provides 10mAcm in the oxygen evolution performance test. -2 A current density of 303 mV is required.

[0042] Comparative Example 1

[0043] In this embodiment, Ru elemental material was prepared in the same manner as in Example 1, except that selenium powder was not added. The specific steps are as follows:

[0044] (1) 0.05 g of RuCl3·xH2O was dissolved in 35 mL of deionized water and stirred for 10 min. 2 mL of 85 wt% hydrazine hydrate was added dropwise under stirring and stirred for 30 min. The mixture was transferred to a 50 mL Teflon reactor and hydrothermally reacted at 180 °C for 12 h. After the reaction, the mixture was centrifuged, washed, and dried to obtain Ru(OH)3.

[0045] (2) Ru(OH)3 powder was calcined at 650℃ for 3h under argon atmosphere to obtain Ru material.

[0046] Figure 5 This is the XPS graph of the Ru material obtained in this comparative example without adding selenium powder. It can be seen from the figure that there is no RuSe2 in the material.

[0047] The electrolytic water oxygen evolution performance of the Ru material obtained in this example was tested in the same manner as in Example 1. Figure 6 As shown, it can be seen that 10mAcm -2 For a current density of 100 mV, Ru requires an overpotential of 285 mV.

[0048] Comparative Example 2

[0049] In this embodiment, RuSe2 material was prepared in the same manner as in Example 1, except that 85 wt% hydrazine hydrate was not added dropwise. The specific steps were as follows:

[0050] (1) 0.05 g of RuCl3·xH2O was dissolved in 35 mL of deionized water. 0.05 g of selenium powder was added under vigorous stirring and stirred for 30 min. The mixture was transferred to a 50 mL Teflon reactor and hydrothermally reacted at 180 °C for 12 h. After the reaction, the mixture was centrifuged, washed, and dried to obtain RuSe2.

[0051] (2) The dried powder was calcined at 650 °C for 3 h in an argon atmosphere to obtain RuSe2 material.

[0052] The electrolytic water hydrogen evolution performance of the RuSe2 material obtained in this embodiment was tested in the same manner as in Example 1. Figure 7 As shown in the figure, it can be seen that when the voltage reaches -0.4V (vsRHE), the current density reaches -41mAcm -2 .

[0053] In summary, Ru / RuSe2 heterojunction can improve the performance of water electrolysis and oxygen evolution reaction (OER): under acidic conditions, 10mAcm -2 The current density only requires 268mV overpotential, which is better than the 285mV required for pure Ru materials; hydrogen evolution reaction (HER): the current density reaches -63mAcm at a voltage of -0.4V (vsRHE) -2 , significantly higher than the -41mAcm required for pure RuSe2 material -2By utilizing the synergistic effect of Ru and RuSe2, the optimal catalytic benefit is achieved under controllable costs. The Ru / RuSe2 heterojunction interface is regulated by electron transfer, so that the Ru site optimizes the adsorption capacity for HER activity, and the RuSe2 site promotes the conversion of intermediates in the OER process, achieving a dual effect in one dose, which can effectively improve the performance of hydrogen and oxygen evolution in water electrolysis; by utilizing the synergistic effect of Ru and Se, the amount of precious metals is reduced while maintaining high activity, the catalyst cost is controllable, and it meets the needs of industrial applications; the hydrothermal-calcination two-step process is simple, the parameter range is clear, it is easy to scale up production, and the performance is stable between batches.

[0054] It is understood from common technical knowledge that the present invention may be implemented by other embodiments that do not depart from its spirit or essential features. Therefore, the embodiments disclosed above are, in all respects, merely illustrative and not exclusive. All modifications within the scope of the present invention or equivalent to the scope of the present invention are intended to be encompassed by the present invention.

Claims

1. A ruthenium / ruthenium selenide composite material and a preparation method thereof, characterized in that: The following steps are involved: The ruthenium salt is dissolved in deionized water, selenium powder is added under vigorous stirring, and then a reducing agent is added and stirred evenly. The mixture is then transferred to a reactor for a hydrothermal reaction. After the reaction is completed, the mixture is centrifuged, washed, and dried. The resulting product is sintered under an inert atmosphere to obtain a Ru / RuSe2 composite material.

2. The ruthenium / ruthenium selenide composite material and the preparation method thereof according to claim 1, characterized in that: The specific steps include: S1. Dissolve 0.05-1 g of ruthenium salt in 35 mL of deionized water, add 0.05-1 g of selenium powder under vigorous stirring, and stir for 5-15 minutes to form a mixed solution; S2. Add 2-5 mL of 85 wt% hydrazine hydrate or 0.5-1 g of NaBH4 as a reducing agent to the mixed solution in S1 and continue stirring for 20-30 min; S3, transfer the stirred solution in S2 to a 50 mL Teflon reactor for hydrothermal reaction; S4. After the hydrothermal reaction is completed, the product is centrifuged, washed, and dried to obtain a Ru(OH)3 / RuSe2 intermediate; S5. The Ru(OH)3 / RuSe2 intermediate obtained in S4 is calcined at 500-700°C for 3-4h under an inert atmosphere to obtain a Ru(OH)3 / RuSe2 composite material.

3. The ruthenium / ruthenium selenide composite material and the preparation method thereof according to claim 2, characterized in that: The ruthenium salt used in step S1 is any one of RuCl3·xH2O, anhydrous ruthenium chloride or ruthenium acetate.

4. The ruthenium / ruthenium selenide composite material and the preparation method thereof according to claim 2, characterized in that: The temperature of the hydrothermal reaction in step S3 is 150-180° C., and the reaction time is 10-15 hours.

5. The ruthenium / ruthenium selenide composite material and the preparation method thereof according to claim 2, characterized in that: The inert atmosphere used in step S5 is argon or nitrogen.

6. The ruthenium / ruthenium selenide composite material and the preparation method thereof according to claim 5, characterized in that: The inert atmosphere is preferably argon.

7. A Ru / RuSe2 composite material obtained by the preparation method according to any one of claims 1 to 6, characterized in that: The Ru / RuSe2 composite material is a hexagonal stable phase material.

8. Use of the ruthenium / ruthenium selenide composite material obtained by the preparation method according to any one of claims 1 to 6 or the ruthenium / ruthenium selenide composite material according to claim 7 as a catalyst in hydrogen production by electrolysis of water.

Citation Information

Cited By

  • Iridium-selenium catalyst as well as preparation method and application thereof

    CN120866876A